Thai Wisdom Management for Health Tourism Development in Thailand - Muenchan, Nutchanat; Pimonsompong, Chalongsri; Buddhabhumbhitak, Ketwadee; Dabphet, Siripen (JOURNAL OF SOUTHERN TECHNOLOGY, 2018)
This research aims 1) to study the components of the excellence of Thai wisdom in the health tourism context, 2) to study the process of Thai wisdom management in health tourism in Thailand and 3) to propose a model of Thai wisdom management of health tourism in Thailand. This research is a mixed methods research, the data were collected by 851 questionnaires and received 429 questionnaires. Purposive sampling was used as a tool for informant selection. 30 In-depth interviews and 30 focus group discussions with the representatives from local government and private sectors who were directly involved in the development of health tourism and the representatives from the health tourism community, including community leaders, local people, philosophers, and health tourism entrepreneurs in the community. Purposive sampling was used to select participants. Quantitative data analysis using descriptive statistics, such as mean and standard deviation and qualitative data analysis using content analysis were applied. The results showed that the components of the excellence of Thai wisdom in health tourism were 1) the identity of the local wisdom 2) the use of natural to promote physical and mental health 3) the aesthetic of service 4) the traditional treatment 5) the happiness and the peaceful of people in the community and balance with the natural environment 6) the preservation and transferring knowledge of health wisdom and 7) the presentation of the benefits and quality of the service in health tourism. The secondary, the processes of Thai wisdom management in health tourism in Thailand were identifying wisdom, capturing wisdom, codifying wisdom and wisdom flow. Finally, the Thai wisdom management model are the process of 1) identify unique wisdom, 2) new integration, 3) identity product and 4) creative activity.